Integrating Steam into Tri-N Based Science Learning Devices to Improve Elementary Student’s Creative Dimension - Agung Ardhianto; Ana Fitrotun Nisa; Banun Havifah Cahyo Khosiyono (Universitas Pendidikan Ganesha, 2026)
This research is motivated by the need for innovative learning tools that can enhance the creative dimension of elementary school students. The focus of the research is to develop, test the feasibility, and test the effectiveness of Tri-N-based learning tools integrated with the STEAM approach. The research uses the ADDIE development model with data collection techniques through interviews, observations, and questionnaires. Analysis was conducted qualitatively to describe the development process and quantitatively to test the feasibility and effectiveness of the tools. The results showed that the learning tools in the form of teaching modules, student worksheets, and assessment sheets for the science subject were classified as very feasible, with an average validation score of 3.55 (88.83%). Teacher and student responses also showed a very feasible category. The effectiveness test showed a significant increase in students' creative dimension, with an N-Gain Score in the high category (0.74-0.76), and a t-test showed a significant difference between pre- and post-use scores. In conclusion, Tri-N-based learning tools integrated with STEAM are proven effective in enhancing elementary school students' creativity. These findings underscore the importance of developing innovative tools grounded in a multidisciplinary approach to support 21st-century learning.